Glutelin is partially degraded in globulin-less mutants of rice (Oryza sativa L.) - Tomoyuki Katsube-Tanaka; Nadar Khan; Satoru Yamaguchi; Takeshi Yamaguchi; Shuichi Iida (Plant Production Science, 2016)
Multigenic glutelins and monogenic globulin are major storage proteins accumulating in vacuole-derived protein body (PB-II) of rice (Oryza sativa L.) seeds. Because their interplay in PB-II formation was scarcely known, the effect of globulin-less mutation on glutelin accumulation was investigated. In globulin-less mutants, no phenotypic defect was found in seed and plant growth, while PB-II was deformed and apparent glutelin composition was changed, producing new glutelin α polypeptides X1–X5. 2D-PAGE of different combinations of globulin-less and glutelin subunit mutations suggested that the X1/X2, X3, and X4/X5 were derived from glutelin GluB1/GluB2/GluB4, GluA3, and GluA1/GluA2 subunits, respectively. Western blot with glutelin GluB4 subunit-specific and its variable region discriminable antibodies indicated at least in part the new spots X1/X2 are partially degraded products of GluB4 α polypeptides by the removal of 2–39 residues from C-terminus. Time course experiments with maturing seeds indicated the partial degradation of GluB4 occurred earlier (from 7 days after flowering) and higher than that of GluA1/GluA2. Considering the above results together with the fact that globulin accumulates at the periphery of PB-II and its absence produces deformed PB-II, globulin protects glutelins from proteinase digestion and thereby facilitates stable glutelin accumulation.